EFICIÃŠNCIA DA MANIPUEIRA NO CONTROLE DO ÃCARO-BRANCO DO MAMOEIRO (NOTA PRÃ‰VIA) - Ponte, J. JÃºlio da (REVISTA DE AGRICULTURA, 2015)
EFICIÃŠNCIA DA MANIPUEIRA NO CONTROLE DO ÃCARO-BRANCO DO MAMOEIRO (NOTA PRÃ‰VIA)